MASTERING THE PRODUCTION OF A CONTINUOUS CASTING BILLET DIAMETER 200 MM FROM CHROME-MOLYBDENUM STEEL GRADES FOR THE PRODUCTION OF SEAMLESS PIPES AT THE OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - I. А. Bondarenko; I. A. Kovalenko; A. V. Tereshchenko; A. V. Feklistov (Литьë и металлургия)
Growth in demand for drilling and perforated pipes in the Russian Federation and the USA requires an increase in the production of seamless pipes. In turn, the specific operating conditions of the pipes present special requirements to the product for strength and resistance in aggressive media. This article describes the experience of mastering the production of continuous casting billets from chromium-molybdenum steel grades at the OJSC «BSW – Management Company of the Holding «BMC».